Current State and Prospects of Development of the Services Market in Ukraine (Economic journal of Lesya Ukrainka Volyn National University, 2015)
The article deals with the role of the sphere of services and its importance in the country economy. In particular, the deterioration of the market for laundries and dry cleaners, repair shops, restaurant market, market beauty salons, corporate insurance market and telephony services. The emphasis is on the most promising development of tourism, market advertising and marketing services market. Attention is paid to assessing the status and perspectives of the market services development gas stations, telecommunications market syndicated lending and leasing, franchising and consulting activities. The article also discussed the potential for the development of international trade in services, in particular exports of services.
Keywords: sphere of services, development of sphere of services, problems and perspectives of development